Monoaminergic mediation of hyperalgesic and analgesic descending control of nociception in mice - Nemoto,W; Kozak,D; Sotocinal,SG; Tansley,S; Bannister,K; Mogil,JS (Pain, 2023)
Abstract Descending control of nociception (DCN; also known as conditioned pain modulation [CPM], the behavioral correlate of diffuse noxious inhibitory controls) is the phenomenon whereby pain inhibits pain in another part of the body and is the subject of increasing study because it may represent a biomarker of chronic pain. We recently discovered that pain modulation on the application of a DCN paradigm involving low-intensity test stimuli occurs in the direction of hyperalgesia in healthy mice and rats, whereas the use of high-intensity stimuli produces analgesia. To elucidate the physiological mechanisms underlying hyperalgesic DCN, we administered agonists and antagonists of norepinephrine (NE) and serotonin (5-HT) receptors, key neurochemical players in the production of analgesic DCN. We find that 3 different monoamine reuptake inhibitors—the NE-selective reboxetine, the 5-HT-selective fluoxetine, and the dual NE/5-HT agonist duloxetine—all abolish hyperalgesic DCN when administered into the spinal cord (but not systemically), with no effect on heat or mechanical pain sensitivity. The reversal by reboxetine of hyperalgesic DCN is mediated by α 2 -adrenergic receptors (ie, blocked by atipamezole), and the fluoxetine reversal is mediated by 5-HT 7 receptors (ie, blocked by SB269970). By contrast, analgesic DCN was found to be reversed by atipamezole and SB269970 themselves, with no effect of reboxetine or fluoxetine. Thus, hyperalgesic DCN seems to be the neurochemical opposite to analgesic DCN. These data further validate and help elucidate a preclinical paradigm that mimics dysfunctional CPM and thus may form the basis of translational experiments that aim to reveal preventative pharmacological strategies for individuals predisposed to persistent pain.